Strengthening national food control systems : a quick guide to assess capacity building needs - Hopper, Marlynne (FAO RomeIT, 2007)
Seeks to enable countries to evaluate the performance of the existing food control system from the perspective of different stakeholders, to generate a medium-term vision of an improved food control system, and to identify capacity building needs and options to address them.